Analisis Kemampuan Siswa Kelas 11 MA Daarul Uluum Lido Memecahkan Soal Baris dan Deret Via Google Form - Vivi Hariyanti Safitri; Supardi Supardi; Faisal Suhendi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The research conducted at MAS Daarul Uluum Lido Bogor Jl. Mayjen Hr Edi Sukma KM 22, Ciburuy Village, Cigombong District, Bogor Regency, aims to analyze the level of Mathematical Problem Solving Ability in the Sequence and Series Material of Class 11 at MA Daarul Uluum Lido through Google Form Media. The research method used is qualitative research with the sampling technique used is purposive sampling. The target population in this study were all class 11 students at MAS Daarul Uluum Lido. The accessible population in this study was only class 11 D MIA MAS Daarul Uluum Lido students. The research sample was 6 students, consisting of 2 students with low-level mathematical problem solving abilities, 2 students with medium-level mathematical problem solving abilities and 2 students with high-level mathematical problem solving abilities. The data analysis technique was carried out descriptively qualitatively before and during the field, namely data reduction analysis, data presentation and drawing conclusions and data verification. Based on the results of the study, it can be concluded that students in the low category are 2 students with a percentage of 5.55%, 28 students with a percentage of 77.77% are in the medium category and 6 students with a percentage of 16.6% are in the high category. So the dominant ability of solving mathematical problems in the material of Sequences and series at MAS Daarul Uluum Lido is in the medium category with a percentage of 77.77%.